Estimation of Salivary Glucose levels as a Diagnostic aid for Diabetes Mellitus - Chouhan, Shweta; Kallianpur, Shreenivas; Tijare, Manisha; Prabhu, Tukaram; K, Sowmya; Gupta, Sandeep (Biology, Engineering, Medicine and Science Reports)
Aim: The present study was designed to correlate the serum and salivary glucose levels and estimate associated salivary parameters (such as salivary flow rate, pH and buffering capacity) among diabetic and healthy individuals. Settings and Design: 80 patients were included in this study of which 30 patients were uncontrolled diabetics (group I), 30 patients were controlled diabetics (group II) and 20 patients were healthy individuals (group III). Materials and Methods: Salivary and serum glucose levels and salivary flow rate were measured using established methods. Results: The mean serum glucose was higher in group I as compared to group II and group III. In all the groups, salivary glucose levels significantly correlated with serum glucose levels. A statistically significant correlation was also observed between salivary glucose and salivary flow rate in all the three groups. The mean pH values were similar in all the three groups, indicating unaltered salivary buffering capacities. Conclusion: Salivary glucose levels may be used as an alternative and reliable index in diagnosis of diabetes mellitus.
Keywords: Diabetes; Saliva; Diagnostic tool; Glycemia; Non-invasive diagnosis; patient care